Efektivitas Kadar Gula Darah Sebelum Dan Sesudah Melalui Senam Diabetes Pada Penderita Diabates Melitus Tipe 2 - Rusli Taher (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
The research objective: to determine the effectiveness of blood sugar levels before and after going through diabetes exercises in people with diabetes mellitus type 2 at the Kapasa Health Center, Makassar City. Methods: The research method uses quantitative research using Quasi Experiment research design, which is an impure research design using all subjects in the group to be treated (treatment), instead of using randomly drawn subjects, the research design used is the One Group design. pretest posttest. The sampling technique in this study used accidental sampling. Accidental sampling is sampling carried out by taking respondents who happen to be available or available in a place according to the context of the study3. Results: The results showed that of the 25 respondents studied, there was an effect of blood sugar levels before and after giving diabetes exercises at the Kapasa Public Health Center in Makassar City in the first week with a value of p = 0.027 <0.05. There is an effect of blood sugar levels before and after giving diabetes exercises at the Kapasa Public Health Center in Makassar City on week II with a value of p = 0.003 <0.05. There was no effect of blood sugar levels post week I and blood sugar levels post week II given diabetes exercises with a value of p = 0.563 <0.05. Discussion: Patients with diabetes mellitus who are more focused and only prioritize diet management and taking medicines, even though regular diet management does not guarantee the control of blood sugar levels, but this must be balanced with appropriate physical exercise. Because if people with diabetes mellitus do not do physical activity, muscle metabolism occurs only a little, so that the use of glucose in the blood is reduced, this can cause a buildup of glucose in the blood, so that glucose levels in the blood are high1. Conclusion: There is an effect of blood sugar levels before and after weeks I and II at the Kapasa Public Health Center, Makassar City. Suggestion: The results of this study can provide input for nurses who are on duty at the Kapasa Public Health Center in Makassar City, so that they always provide motivation and encouragement to diabetics in matters related to diabetes exercise whose purpose is to cure the disease.